PERAN ETNOMATEMATIKA DALAM PEMBELAJARAN MATEMATIKA - Rajiun Siregar; Suparni Suparni (JURNAL MathEdu (Mathematic Education Journal), 2026)
Abstract This study aims to determine the effectiveness of ethnomathematics-based learning in mathematics learning. This research is a library research with a qualitative approach. The method of collecting data is by means of document studies and analyzed by technical descriptive analysis. Library research is research whose data comes from books, dictionaries, documents, magazines, journals and so on. (Harahap, 2014) While the analytical technique used is descriptive analysis technique by looking at research data that has been done by previous people related to ethnomathematical research. This is evidenced by research studies that have been carried out by researchers who have done previously which will be mentioned in the discussion of this research. Therefore, ethnomathematics can be used by teachers in conducting effective and fun learning, besides that ethnomathematics can improve students' mathematical abilities such as the results of research that will be discussed in this discussion and can increase the love of students to understand their own culture.